Class Struggle and Religious Difference in the Workplace: The Politics of Representing Islam in Rabah Ameur‐Zaïmeche's Dernier maquis (2008). Issue 4 (December 2013) - Higbee, Will
<x xml:space="preserve">Abstract</x> The aim of this article is to explore how the 2008 film Dernier maquis, by Maghrebi‐French director Rabah Ameur‐Zaïmeche, attempts to correct a perceived absence in French cinema of Islam by focusing its narrative on the conflict that ensues between Mao, a French Muslim boss, and his Muslim immigrant workers, when Mao unilaterally appoints an imam to preside over the mosque he has constructed for his workers in a pallet yard located on a remote industrial estate on the outskirts of Paris. The article analyzes how, in Dernier maquis, Ameur‐Zaïmeche combines issues of class struggle and exclusion of the immigrant worker in contemporary France, with the potentially problematic place of ethnic and religious difference within the Republican nation.